PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN LIVEWORKSHEET UNTUK MENINGKATKAN HASIL BELAJAR PENYAJIAN DATA - Amanda, Lola; Suciana, Fadila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of students at SDN 06 Batu Taba due to the limited use of effective learning models and media by teachers. One alternative model is Problem-Based Learning, which encourages students to think critically in solving problems, supported by Liveworksheet as a digital worksheet for data presentation learning. This study aims to describe the improvement in data presentation learning outcomes through the use of a Liveworksheet-assisted Problem-Based Learning model in grade V at SDN 06 Batu Taba. This research employed classroom action research (CAR) using qualitative and quantitative approaches and was conducted in two cycles: cycle I (two meetings) and cycle II (one meeting). Each cycle consisted of planning, implementation, observation, and reflection. The research instruments included observation sheets, tests, and non-test instruments. The research subjects were teachers and 27 fifth-grade students at SDN 06 Batu Taba, consisting of 11 boys and 16 girls. The results showed an improvement in the RPPM, with an average score of 85.4% (B) in cycle I, increasing to 95.8% (SB) in cycle II. Teacher activity improved from 87.5% (B) to 95% (SB), while student activity increased from 82.5% (B) to 95% (SB). Student learning outcomes also improved, from an average score of 64.56 (D) in cycle I meeting 1 to 76.5 (C) in meeting 2, and further increased to 85.07 (B) in cycle II. These findings indicate that the Liveworksheet-assisted Problem-Based Learning model improves fifth-grade students’ learning outcomes at SDN 06 Batu Taba.